The Mothers’ Club of Cambridge, 1878-1904: Reappropriating, Reconfiguring and (Re)presenting Expert Knowledge of Mothering - Rawlins, Roblyn (Journal of the Motherhood Initiative for Research and Community Involvement, 2014)
Expert knowledge such as prescriptions for motherhood devalues local/traditional knowledge, yet practitioners of local knowledges such as mothers may resist this,often through the reappropriation of expert knowledges. To illustrate the processes of reappropriation, reconfiguration, and representation of expert knowledges of motherhood, I present a case history of the Mothers’ Club of Cambridge, Massachusetts, uncovering the process whereby this group of mothers created a space within expert discourse for reassertion of their own experiential expertise. The club functioned as anode between expert discourse and everyday practice by reviewing the child rearing prescriptions of established experts, reappropriating this knowledge by testing it experientially, and reconfiguring it to suit their local milieu. This reappropriation and reconfiguration culminated in the (re)presentation of expert knowledge as themembers began delivering expert lectures to local settlement house mothers andpublished their own advice book. For the settlement house mothers, the Mothers’ Club constituted an intermediary set of experts. For its members, the Mother’s Clubof Cambridge constituted a site through which generations of mothers supportedone another in their mothering work by providing space in which to negotiatethe tension between their local and experiential knowledge as mothers and expertknowledges of childrearing.